Mobile agents and their use for information retrieval a brief overview and an elaborate case study. - Glitho, R.H.
Mobile agents emerged in the mid-1990s, and have raised considerable interest in the research community. The proponents associate several benefits with their use. However, there are still very few quantitative measurements to back the claimed benefits. This article is devoted to mobile agents and their use for information retrieval. We provide a brief overview and an elaborate case study. The overview introduces the concept of mobile agent, enumerates the claimed benefits, and reviews the hindrances to widescale deployment. It also discusses the state of the art of mobile-agent-based information retrieval, including the very few quantitative studies that exist. Our case study is on information retrieval from electronic calendars for multiparty event scheduling. Many events require the participation of several parties. Prior knowledge of the date when most (if not all) targeted participants are available is often a prerequisite for scheduling them. However, identifying this date can easily turn into a nightmare, especially when the number of targeted participants is large. Nowadays, electronic agendas (e.g., MS Outlook) are stored on servers. An application can access them, retrieve information on the availability of the targeted participants, and derive the date from the information. In the case study, a mobile agent is dispatched in the network, instead of retrieving the information using the client/server paradigm. The agent visits the servers, accesses the agendas, retrieves the information, and identifies the date. Finding a date suitable for several potential participants may require the rescheduling of some events that have been previously arranged by some participants. We propose the use of agents that act as the personal agents of the participants for the negotiation inherent to this rescheduling. The measurements we have made indicate clearly that the mobile-agent-based approach outperforms its client/server counterpart even when the latter is optimized. These results can easily be transposed to most information retrieval applications, and demonstrate, for this specific application domain, the performance benefit associated with mobile agents. We now dispatch a single agent in the network. In the future, we will dispatch several agents
Keywords: Ethernet LAN; MS Outlook; Client/server paradigm; Electronic agendas; Electronic calendars; Information retrieval; Mobile agents; Multiparty event scheduling; Network load data analysis; Personal agents